Fasilitasi Masyarakat Dukuh Kerep Desa Wagir Kidul Dalam Pemanfaatan Limbah Minyak Jelantah Kolaborasi Dengan Gudang Limbah Nabati - Binti Choirul M (Social Science Academic, 2025)
Daily necessities require people to work and make money. And Industry is one of the MSME assets in Wagir Kidul Village, and from this, industrial waste in the form of used cooking oil emerges. Which used cooking oil is also an impact from the community from the results of making daily kitchen preparations. Therefore, so that the community can use used cooking oil as something even more useful, the author took the initiative to create a used cooking oil waste utilization program branded as a used cooking oil brand, this program as a collection of used cooking oil waste so that it can be more useful and have more usefulness for the community. This research uses the ABCD Method where the stages in this method are 1. Inculturation, 2. Discovery, 3. Design, 4. Define and the last 5. Reflection. The result of this service is the Work Program for the use of used cooking oil as biodiesel material in collaboration with the Vegetable Waste Warehouse. From the existing potential and enthusiasm of the community with this program, the author can simultaneously educate the public about the dangers of used cooking oil waste for health and the environment.